2021
DOI: 10.1007/s10049-021-00870-4
|View full text |Cite
|
Sign up to set email alerts
|

Die Ausbildung von Lehrerinnen und Lehrern als Multiplikatoren für den Wiederbelebungsunterricht an Schulen

Abstract: Zusammenfassung Zielsetzung Die Einführung des Wiederbelebungsunterrichts an Schulen soll die Reanimationsbereitschaft in der Gesellschaft und das Überleben von Menschen mit einem außerklinischen Herz-Kreislauf-Stillstand nachhaltig verbessern. Ziel der vorliegenden Untersuchung war es zu prüfen, wie Lehrkräfte als qualifizierte Multiplikatoren den Wiederbelebungsunterricht in ihren Schulen eigenständig durchführen. Methodik Die Uniklinik Köl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…We found 12 Editorials [1–12], 9 ‘Letters to the Editor [13–21]’, 2 ‘Special Reports [22–23]’, 4 Reviews [24–27], 2 Guidelines [28,29 ▪▪ ], 9 Original Articles [30–36,37 ▪ ,38 ▪ ], and 17 Conference or Poster Abstracts [39–55], which are in Table 1. Among the nine original articles, we found three randomized controlled trials (RCT), two longitudinal studies and four cross-sectional studies (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found 12 Editorials [1–12], 9 ‘Letters to the Editor [13–21]’, 2 ‘Special Reports [22–23]’, 4 Reviews [24–27], 2 Guidelines [28,29 ▪▪ ], 9 Original Articles [30–36,37 ▪ ,38 ▪ ], and 17 Conference or Poster Abstracts [39–55], which are in Table 1. Among the nine original articles, we found three randomized controlled trials (RCT), two longitudinal studies and four cross-sectional studies (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The other cross-sectional study [32] with students showed few proportions of the boys (aged 12–14 years) and girls (aged 14–16 years) reached the proper compression depth (5–6 cm), making final considerations that to acquire CPR skills, more exertion and training are needed for younger children and adolescents. The fourth cross-sectional study [36] found that schoolteachers are slightly more effective than medical staff to improve students’ CPR knowledge and skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trained teachers are very reliable in implementing CPR education in their schools. 47 The multiplier effect, the number of trained schoolchildren per trained teacher, is 38 47 and effectiveness of the training was proven by Felzen et al 48 Another approach to the systematic education of schoolteachers in CPR is integrating mandatory CPR education into the routine training syllabus of teachers. 10,39,40,49 This would support systematic CPR education of schoolchildren, the main goal of the KIDS SAVE LIVES-statement, instead of CPR training as part of voluntary campaigns and projects.…”
Section: Level 4: Facilitators and Barriers Regarding Individual Schoolsmentioning
confidence: 99%
“…They are considered as the ideal multipliers for resuscitation training in schools. 4 Schoolteachers core competency is to adequately teach skills, knowledge, and behavior as they learned didactics and methodologies for children's teaching. Thus, who better than them to teach BLS to schoolchildren?…”
mentioning
confidence: 99%